The effect of anxiety and nutritional habits on the body distortion of athletes - Ramírez-Goerke, M. I.; Tornero-Aguilera, J. F.; Martín-Rodríguez, A.; Clemente-Suárez, V. J. (Nutrients, 2025)
Background: Anxiety disorders have been rising globally, particularly among adolescents and women. However, the relationship between diet, psychological traits, and anxiety levels in athletes remains underexplored.